10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
One in 3 US women of reproductive age live in states that restrict abortion. Total or near-total abortion bans exempt cases where the health or life of the pregnant person is threatened. However, exemptions are ambiguously defined, and abortion practitioners risk criminal prosecution if they are judged after the fact to have performed a prohibited abortion. To describe hospital policies and practices for exempted abortions. Qualitative study conducted between June and December 2025. The top 5 hospitals by birth volume in abortion-restrictive states (hospitals in states with total or 6-week abortion bans as of June 2025) were identified and participants from 1 hospital per state who were responsible for making or implementing hospital abortion policies were sequentially enrolled. Two coders conducted content analysis of semistructured interviews investigating how hospitals remained apprised of current state laws, supported evidence-based exempted abortion care and reproductive care, and protected clinicians. Thirty-four participants from 9 hospitals (mean [SD] annual live births, 5257 [3289]) across 9 states were most commonly physicians (16 participants [47.0%]) or hospital administrators (10 participants [29.4%]). Participants identified the following hospital policies or practices as supporting evidence-based reproductive care within legal constraints: (1) providing criminal defense resources for physicians; (2) implementing additional employee protections, such as online threat monitoring, contractual indemnity clauses, and coverage for out-of-state abortions for employees; (3) explicitly aligning institutional definitions of abortion with the fullest extent of care permitted under state law to avoid unnecessarily restrictive care; (4) formalizing decision-making support for exempted abortions (eg, multidisciplinary committees); (5) building intrastate hospital alliances to standardize interpretation of state laws banning abortion; and (6) engaging in legislative advocacy and strategic litigation to maximize reproductive care. Participants reported multiple policy effects, including greater employee retention and recruitment and more timely and expansive reproductive care. In this qualitative study of 9 high birth-volume hospitals in 9 abortion-restrictive states, institutions implemented policies to protect their employees and support the fullest extent of legally permissible, evidence-based reproductive care. Identified policies may be instructive to other hospitals that provide legally contested medical care.